Table of contents, editorial board, and other front matter - James P. Chapman (Journal of Applied Communications, 1978)
Editorial front matter and table of contents for vol.61, no.1, Jan-Mar (1978) of ACE, the official journal of the American Association of Agricultural College Editors.